Political leaders in Singapore : a content analysis of attributes and trends. - Lam, Yun Leei. (2008)
We analysed the Attributes of the Political leaders in Singapore namely SM Lee, PM Goh, BG Lee, Parlimentary Sect Chan Soo Sen, NMP Claire Chiang, and 2 student union leaders (1999-2000).